PSIKOEDUKASI ONLINE UNTUK MEREDAKAN STRES DI TENGAH PANDEMIK COVID-19 - Pesau, Heni Gerda; Panglewai, Meidy M.L. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
The COVID-19 pandemic has caused many changes in various aspects of people's lives. The changes caused psychological problems, one of which is stress. Stress conditions experienced by individuals need to be handled so as not to prolong or cause other psychological symptoms. One of the interventions that can be done in the midst of a pandemic is online psychoeducation. Based on this, the target of online psychoeducation carried out was the general public who were willing to become participants. The goal of online psychoeducation activities was to increase participants' knowledge of stress conditions and techniques that can be used to relieve stress. Psychoeducation was given in two methods, namely interactive lectures that discussed stress recognition and modeling techniques related to stress relief techniques. The results of the evaluation of the activities showed that more than 50% of participants gave positive responses to the material presented and the participants' expectations were achieved after participating in online psycho education. Thus it can be concluded that providing online psychoeducation could provide knowledge related to stress conditions experienced and techniques that can be applied to relieve stress experienced during the current COVID-19 pandemic. Keywords: COVID-19, Stress, Psychoeducation, Online, Technique